Filosofía feminista y escenarios teatrales recientes: Argentina 2013-2015 - Proaño Gómez, Lola (Latin American Theatre Review, 2018)
This article considers Latin American feminist theatrical production, specifically from Argentina, to answer the question of whether the evolution of feminist philosophical theory has impacted Latin American theatre. To this end, the study examines Mecánicas (2013) by Celina Rosenwurcel and Esquinas en el cielo (2013) by Mariana Mazover. Unlike the productions of the 1980s, which featured the idea of a feminine essence, these recent productions stage the female subject in light of the spaces gained via deconstructionism in recent years, but they also show new difficulties that stem from the expansion of capitalism and its instrumental rationality. This article takes a feminist point of view, following Marxist feminist philosophy and its reflection on the patriarchal capitalist structure as well as theory of intersectionality. It concludes that considerations made through gender insufficiently explore the status of women today and that the analysis of feminist theatre needs to expand its view to include other philosophical categories that allow for more complex, nuanced readings and a better understanding of our times.